Designing Customer Co-Creation: Business Models and Co-Design Activities - Gembarski, Paul Christoph; Lachmayer, Roland (International Journal of Industrial Engineering and Management, 2017)
For nearly 30 years, mass customization as a competitive strategy has overcome the oxymoron of developing and marketing individualized products with the efficiency and at a price of mass productiongoods. Most authors agree that solution space development in general and product configuration in particular are two key tools for the success of this competitive strategy. Especially product configurators represent a customer co-design tool, which helps customers to express their needs and translate them into a valid technical specification. But also for product-service-systems co-design is a powerful tool to learn about customers and monitor their requirements. In this article, the relation between competitive strategy, business model, customization strategy and design solution space of mass customizers and suppliers of product-service-systems is investigated. Taking the interaction between customer and design department as a basis, templates for different co-design activities are derived that document what kind of solution space elements, knowledge and significant production strategies should be considered for different degrees of customization. This is then discussed with regard to an exemplified co-design business model for a customizable tea brewing machine. Article history: Received (06.02.2017); Revised (04.05.2017); Accepted (03.07.2017)